Academic Marketing Climate, Marketing Strategies And Student Enrollment Turnout Of Council Admission And Marketing In Selected Schools In District 1 Province Of Laguna - Lazanas, Suzette H.; Urbina, Marilou C. (Technium Social Sciences Journal, 2023)
The ultimate purpose this study aimed at providing recommendations for implementing higher education marketing techniques directed at prospective students. The major concerns of this study was to determine the academic marketing climate, level of effectiveness of marketing strategies, and level of enrollment turnout of council admission and marketing in District 1 in the province of Laguna. This study used the descriptive correlation design since it determined relationship between academic marketing climate, marketing strategy and enrollment turnout f council admission and marketing in selected schools in District 1 Province of Laguna. The marketing management of the selected schools in the District 1 Province of Laguna were able to develop and maintain successful relationships with its target students by providing a safe and conducive environment for learning. There was a very effective utilization of marketing strategies in terms of accessible place, providing quality services, usage of technology, and usage of media/social media platforms. The enrollment turnout of council admission and marketing in selected schools in District 1 Province of Laguna increases every year. Academic Marketing Climate and Marketing Strategies are significant predictors of enrolment turnout. This implies that the favorable the academic marketing climate and the higher the level of effectiveness of marketing strategies, the more possibility that there will be an increase in the level of enrolment turnout.